Dynamic variations in infrared skin temperature of weaned pigs experimentally inoculated with the African swine fever virus: A pilot study - Sang-Ik Oh; Hu Suk Lee; Vuong Nghia Bui; Duy Tung Dao; Ngoc Anh Bui; Thanh Duy Le; Minh Anh Kieu; Quang Huy Nguyen; Long Hoang Tran; Kyoung-Min So; Seung-Won Yi; Eunju Kim; et al. (MDPI, 2021)
African swine fever (ASF) is a devastating viral disease in pigs and is therefore economically important for the swine industry. ASF is characterized by a short incubation period and immediate death, making the early identification of ASF-infected pigs essential. This pilot-scale study evaluates whether the infrared thermography (IRT) technique can be used as a diagnostic tool to detect changes in skin temperature (Tsk) during the early stages of disease development in experimentally ASF-infected pigs. Clinical symptoms and rectal temperatures (Tcore) were recorded daily, and IRT readings during the experimental ASF infection were analyzed. All infected pigs died at 5–8 days post inoculation (dpi), and the incubation period was approximately 4 dpi. The average Tcore increased from 0 dpi (38.9 ± 0.3 °C) to 7 dpi (41.0 ± 0.5 °C) and decreased by 8 dpi (39.8 ± 0 °C). The maximum Tsk of ASF-infected pigs increased from 2 (35.0 °C) to 3 dpi (38.5 °C). The mean maximum Tsk observed from three regions on the skin (ear, inguinal, and neck) significantly increased from 2 to 3 dpi. This study presents a non-contact method for the early detection of ASF in infected pigs using thermal imaging at 3 days after ASF infection.